2013
DOI: 10.1074/jbc.m111.310029
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin 3A Binds to the Perineuronal Nets via Chondroitin Sulfate Type E Motifs in Rodent Brains

Abstract: Background: Semaphorin3A (Sema3A) is an axon guidance molecule present in the CNS extracellular matrix and on the perineuronal nets (PNNs). Results: Sema3A interacts with chondroitin sulfate E (CS-E) for anchoring to the PNNs. Conclusion:The binding of Sema3A to CS in the PNNs presents a novel mechanism of PNNs in restricting plasticity. Significance: This finding suggests a novel candidate for intervention in promoting CNS recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
138
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(143 citation statements)
references
References 57 publications
(79 reference statements)
2
138
0
Order By: Relevance
“…Vo et al recently demonstrated that Sema3A colocalized with parvalbumin-positive perineuronal nets (PNNs), which are extracellular matrix structures that circumvent inhibitory interneurons, as well as with the CS-DS proteoglycans aggrecan, versican, phosphacan, and tenascin-R [33] (Figure 2), and strongly interacted with CS-DS chains specifically containing E-units [34 ]. The inhibition of neurite outgrowth of dorsal root ganglia by Sema3A was previously shown to be enhanced by the addition of glycosaminoglycans from PNNs [34 ]. Furthermore, a treatment with chondroitinase ABC markedly facilitated plasticity in the visual cortex, injured cortical neurons, and spinal cord injury [35,36].…”
Section: Cs-pgs and Cs-e Are Involved In Neuronal Plasticitymentioning
confidence: 99%
“…Vo et al recently demonstrated that Sema3A colocalized with parvalbumin-positive perineuronal nets (PNNs), which are extracellular matrix structures that circumvent inhibitory interneurons, as well as with the CS-DS proteoglycans aggrecan, versican, phosphacan, and tenascin-R [33] (Figure 2), and strongly interacted with CS-DS chains specifically containing E-units [34 ]. The inhibition of neurite outgrowth of dorsal root ganglia by Sema3A was previously shown to be enhanced by the addition of glycosaminoglycans from PNNs [34 ]. Furthermore, a treatment with chondroitinase ABC markedly facilitated plasticity in the visual cortex, injured cortical neurons, and spinal cord injury [35,36].…”
Section: Cs-pgs and Cs-e Are Involved In Neuronal Plasticitymentioning
confidence: 99%
“…1) are the most extensively investigated. Their components include chondroitin sulfate proteoglycans (CSPGs), hyaluronan, tenascin-R, link proteins, Reelin and semaphorin 3A (Carulli et al, 2013b; Deepa et al, 2006; Dick et al, 2013; Matthews et al, 2002; Vo et al, 2013a). CSPGs, the organizers of the ECM, are highly represented in PNNs, with aggrecan, neurocan, brevican, versican and phosphacan among the most abundant (Deepa et al, 2006; Giamanco and Matthews, 2012; Yamaguchi, 2000).…”
Section: Perineuronal Nets: Composition and Association With Distimentioning
confidence: 99%
“…We focus predominantly on evidence based on chondroitin sulfate proteoglycans (CSPGs), one of their main PNN components (Carulli et al, 2007; Deepa et al, 2006; Giamanco and Matthews, 2012). Importantly, other PNN elements, namely Reelin and semaphorin 3A, have been shown to be involved in the pathophysiology of SZ, although not directly as PNN components (Abdolmaleky et al, 2005a; Carulli et al, 2013a; Costa et al, 2001; Dick et al, 2013; Eastwood et al, 2003; Fatemi, 2005; Impagnatiello et al, 1998; Vo et al, 2013b). In particular, Reelin has been extensively investigated for its role in brain development, synaptic regulation during adulthood and involvement in several brain disorders, including SZ and bipolar disorder; although some of these aspects will be mentioned in this review, we refer to comprehensive publications by other groups for details (Abdolmaleky et al, 2005a; Akbarian and Huang, 2006; Barros et al, 2011; Campo et al, 2009; Chen et al, 2005; Costa et al, 2001; Curran and D’Arcangelo, 1998; Dityatev et al, 2006; Eastwood and Harrison, 2006; Fatemi, 2001; Flashner et al, 2013; Folsom and Fatemi, 2013; Franco and Muller, 2011; Frotscher, 2010; Frotscher et al, 2009a, b; Guidotti et al, 2011; Guidotti et al, 2000; Honda et al, 2011; Impagnatiello et al, 1998; Lakatosova and Ostatnikova, 2012; Pesold et al, 1999; Sinagra et al, 2005; Stranahan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…1) [36]. Sema3A also co-localizes with cell surface CSPGs on cortical neurons, increasing the likelihood of Sema3A-neuropilin-1 interaction and axon repulsion [37][38][39]. This interaction can be augmented by the addition of glycosaminoglycans, which decreases neurite outgrowth and increases growth cone collapse [37,38].…”
Section: Semaphorinsmentioning
confidence: 99%
“…This interaction can be augmented by the addition of glycosaminoglycans, which decreases neurite outgrowth and increases growth cone collapse [37,38]. Conversely, digestion of the chondroitin sulfate side chains with chondroitinase ABC releases bound biologically active Sema3A, perhaps illuminating a mechanism contributing to the growth-promoting effects of chondroitinase ABC treatment [28,[37][38][39].…”
Section: Semaphorinsmentioning
confidence: 99%